Boundary Discords in Yoruba Land: A Case of Ise/ Emure Crisis from the Earliest Time - Buhari Lateef Oluwafemi (Polit Journal Scientific Journal of Politics, 2023)
Since communities and families held land in trust for all family members, it was determined that individuals did not own any of it. Boundary and territorial disputes often stem from material or cultural claims; sometimes they may also emerge as a result of fundamental changes in domestic environments. The focus of this study is an attempt to consider disputation involvements or experiences of two communities, Ise - Ekiti and Emure Ekiti about land as traditionally conceived. The study found clearly that boundaries created by the colonial government became a problem for Ise and Emure communities who were not satisfied with the British artificial boundary demarcations in Yoruba land. The cases of artificial boundary demarcation had led to communal clashes and destroyed properties between these communities. A combination of historical, descriptive and interpretative methods of data collection and analysis was adopted. The study used both primary and secondary sources. The primary data was sourced through oral interviews. Here, fieldwork was carried out among the people of Ise/ Orun and Emure. The researcher interacted with the prominent chiefs, elders, and women in different categories. Information collected through life experience formed the bedrock of the primary data. Secondary data was generated from various relevant journal articles, newspapers, magazines, textbooks, archival materials, unpublished theses, dissertations, WACA Report and the internet. The study concludes that up till the recent time, the boundary discord between Ise and Emure has mellowed down their cordial relationship. It is important to state that the WACA judgments need to be taken by the supreme court for interpretations.